Family businesses and globalization in Finland - Jyrki Ali-Yrkkö; Mika Pajarinen; Petri Rouvinen; Pekka Ylä-Anttila (The Research Institute of the Finnish Economy (ETLA), 2007)
This paper studies whether family businesses (FBs) differ from non-family businesses (non-FBs) in various dimensions of globalization with a representative sample of businesses in Finnish manufacturing and private services. FBs and non-FBs are not so different when it comes to export and off-shore (includes both in-house moves and outsourcing) probabilities and intensities. After controlling for other relevant factors, however, family businesses are less likely to have employment abroad and their shares of foreign employment are likely to be lower than their non-family counterparts. FBs' foreign employment may also be qualitatively different: Compared to non-FBs, FBs seem to be more prone to have employment in the neighboring country rather than in ones geographically more distant. The strategic role of FBs' foreign employment also seems to be different, although due to data limitations we are unable to pin down exactly how. FBs are somewhat more likely to increase their overall Finnish employment in the course of the next few years. This overall observation is largely because family businesses are particularly more likely to hire those with somewhat lower levels of formal education, who also initially tend to command a relatively larger share of their employment.
Keywords: G32; L21; L26; M14; 330; Family business; ownership structure; business objectives; globalization; internationalization; exports; off-shoring; foreign employment; Unternehmen; Familienunternehmen; Eigentümerstruktur; Globalisierung; Offshoring; Vergleich; Finnland